AGRICULTURAL ACTIVITIES AS AN ADDITIONAL WORK FOR SHEEP FARMERS IN BULGARIA - Tsvetana HARIZANOVA – METODIEVA; Nikola METODIEV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of the present study is to analyze the agricultural activities (tillage applied and the types of crops grown) as an additional work for sheep farmers in Bulgaria. The information from the survey was gathered from 14 Bulgarian sheep farmers. Out of 14 farmers, 4 of them (29%) alternate autumn crops (maize, wheat, rye, triticale) with spring crops (oats, peas) or with alfalfa, and one farmer leaves cultivated areas fallow every two years due to the increased acidity of the soil. Farmers who do not practice crop rotation mostly grow alfalfa. Two of the farmers (14%) stated that they grow alfalfa as a monoculture. The majority of farmers (87%) grow leguminous fodder for feeding sheep, and half (53%) of farmers grow cereals. Of the tillage methods used for soil preparation among the surveyed sheep farmers, it is the most applied deep ploughing (57.2%), followed by disking (42.8%), shallow ploughing (35.7%) and lastly harrowing (21.5%) and other tillage methods (21.5%). More than half of farmers (64.3%) do not use plant protection products, 28.6% apply conventional products, and 7.1% - products compatible with organic farming. The prevailing part of farmers (42.9%) applied both mechanical and chemical means of control of weeding. Half of the farmers answered that they only fertilize with animal manure.